2018
DOI: 10.1590/1413-81232018235.17112016
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à autopercepção negativa de saúde em mulheres climatéricas

Abstract: The scope of this study was to investigate the prevalence and factors associated with negative self-rated health in menopausal women registered with the Family Health Strategy in a Brazilian urban center. It is a cross-sectional study with a random sample of menopausal women. A validated instrument addressing sociodemographic and behavioral data related to self-rated health status was used. The association between the variables studied and negative self-rated health was assessed by bivariate analysis followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
36

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 29 publications
3
18
0
36
Order By: Relevance
“…Regarding self-perception of health, it was observed that women who reported bad, very bad or regular self-perception of health were 3 times more likely (OR = 3.58, 95% CI = 3.13-4.11) to develop CBP when compared to women who referred to their health as good and very good. It is worth noting that there is a shortage of studies on the subject with women of childbearing age, but a similar result to that found in this study was pointed out in the literature 44 with women in the climacteric phase, where it was verified that 54% of climacteric women evaluated in the study who had CBP referred to negative self-perceived health when compared to those who indicated having a positive self-perception of health 44 .…”
Section: Discussionsupporting
confidence: 88%
“…Regarding self-perception of health, it was observed that women who reported bad, very bad or regular self-perception of health were 3 times more likely (OR = 3.58, 95% CI = 3.13-4.11) to develop CBP when compared to women who referred to their health as good and very good. It is worth noting that there is a shortage of studies on the subject with women of childbearing age, but a similar result to that found in this study was pointed out in the literature 44 with women in the climacteric phase, where it was verified that 54% of climacteric women evaluated in the study who had CBP referred to negative self-perceived health when compared to those who indicated having a positive self-perception of health 44 .…”
Section: Discussionsupporting
confidence: 88%
“…Uma explicação para isso pode ser o fato de as mulheres serem mais atentas, sensíveis e melhor informada em relação à saúde, percebendo-a de maneira global, considerando aspectos biológicos, psicológicos e sociais. Um estudo (11) verificou que as mulheres são mais sensíveis a percepção de dor e desconforto em comparação aos homens, devido a diversos fatores como escolaridade, ausência de trabalho e arranjo familiar.…”
Section: Discussionunclassified
“…[1][2][3] It is a subjective indicator that encompasses people's physical and emotional components, as well as aspects relating to well-being and satisfaction with their own lives. [3][4][5] Self-rated health has characteristics that extrapolate the meaning of health in the strict sense, taking on representativeness with regard to perceptions of the body, and can reflect not only experience of exposure to disease but also knowledge about its causes and consequences. 6 Studies conducted in Brazil and in other countries have used self-rating of health as an indicator of the real or objective state of health of the general population [3][4][5][7][8][9][10] and of occupational groups.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Self-rated health has characteristics that extrapolate the meaning of health in the strict sense, taking on representativeness with regard to perceptions of the body, and can reflect not only experience of exposure to disease but also knowledge about its causes and consequences. 6 Studies conducted in Brazil and in other countries have used self-rating of health as an indicator of the real or objective state of health of the general population [3][4][5][7][8][9][10] and of occupational groups. 6,[11][12][13] This growing use is justified by the relative ease of operationalizing the indicator and also because of its role as a predictor of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%